Adherence to Endocrine Therapy and Racial Outcome Disparities in Breast Cancer. (28th September 2021) - Reeder‐Hayes, Katherine E.; Troester, Melissa A.; Wheeler, Stephanie B.
Abstract: The disparity in outcomes of breast cancer for Black compared with White women in the U.S. is well known and persistent over time, with the largest disparities appearing among women with hormone receptor‐positive (HR+) cancers. The racial gap in breast cancer survival first emerged in the 1980s, a time of significantmen treatment advances in early‐stage breast cancer, including the introduction of adjuvant endocrine therapy. Since that time, the gap has continued to widen despite steady advances in treatment and survival of breast cancer overall. Although advanced stage at presentation and unfavorable biology undoubtedly contribute to racial differences in survival of HR+ breast, treatment disparities are increasingly acknowledged to play a key role as well. The recent recognition of racial differences in endocrine therapy use may be a key explanatory factor in the persistent racial gap in mortality of HR+ disease, and may be a key focus of intervention to improve breast cancer outcomes for Black women. Implications for Practice: Black women with hormone receptor–positive breast cancer experience the greatest racial disparity in survival among all breast cancer subtypes. This survival gap appears consistently across studies and is not entirely explained by differences in presenting stage, tumor biology as assessed by genomic risk scores, or receipt of chemotherapy. Recent research highlights lower adherence to endocrine therapy (ET) for Black women. Health systems and individual providers should focus on improving communication about the importance of ET use, sharing decisions around ET, providing appropriate support for side effects and other ET‐related concerns, and equitably delivering survivorship care, including ET adherence assessment. Abstract : The disparity in outcomes of breast cancer for Black compared to White women in the United States is well‐known. This article examines the factors contributing to these persistent disparities, including biological and access‐related determinants.